2022
DOI: 10.1007/s00500-022-07643-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel analytical approach to micro-polar nanofluid thermal analysis in the presence of thermophoresis, Brownian motion and Hall currents

Abstract: The present study analyzed micro-polar nanofluid in a rotating system between two parallel plates with electric and magnetic fields. The fluid flow study was performed in a steady state. The governing equations of the present issue are considered coupled and nonlinear equations with proper similar variables. Numerical and new semi-analytical methods have been employed to solve the problem to define the exactness of the results. The influence of physical parameters governing the problem is investigated and illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As in previous work mentioned before [6], [7] AGM method suggested that answers of the ODEs can be shown as polynomial shape. In this article the assumption which gave answer suggest that:…”
Section: Verification With Agm Methodsmentioning
confidence: 76%
See 2 more Smart Citations
“…As in previous work mentioned before [6], [7] AGM method suggested that answers of the ODEs can be shown as polynomial shape. In this article the assumption which gave answer suggest that:…”
Section: Verification With Agm Methodsmentioning
confidence: 76%
“…In fig6 with increasing of Hartman number, microrotation profile raised. Interaction on nanoparticles enhances the heat and causes reduction in dynamic viscosity so that velocity will rise.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In a recent paper by Jalili et al (18), the HPM and AGM method was used to resolve thermal problems for micro-polar nanofluids. Alternatively, Jalili et al (19) applied the HPM method to tackle problems related to the movement of a plate submerged in a Newtonian fluid examined through Caputo fractional differential equations. Jalili et al (20) also demonstrated a novel fractional analytical approach to solve time-space fractional equations from oil pollution analysis using HPM.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [ 48 ] studied the flow, heat transfer of three-dimensional unsteady non-Newtonian Ternary hybrid nano-fluid flow with the presence of magnetic field and thermal radiation. Also, many researchers have researched analytical methods [ [49] , [50] , [51] , [52] , [53] , [54] ] (see Table 1 , Table 2 , Table 3 , Table 4 ).…”
Section: Introductionmentioning
confidence: 99%